Applications of lean tools in a small-scale dairy farm - Ussuna, Guilherme Andrade [UNESP]; Satolo, Eduardo Guilherme [UNESP]; Mac-Lean, Priscilla A. B. [UNESP] (IGI Global, 2022)
Lean production is recognized as an administrative approach associated with a minimization or constant waste system that reduces production and the lean production system. Implementation through tools help various areas of the organization. Although conceptually disseminated and applied in various sectors of the economy, publications in the agribusiness sector are scarce. This chapter presents the results of the application of es lean, action research carried out with a small-scale dairy producer. Through the use of lean tools, such as a flowchart, Ishikawa diagrams, value stream mapping, and the PDCA cycle, it was possible to guide a set of improvements in the property under study, adding profitability gains.